(untitled) (Research, Society and Development, 2021)
This study synthesizes the literary findings related to the daily interaction of elderly people who share the same home with their families. For this, an Integrative Literature Review was carried out in the databases of the Virtual Health Library (VHL), which considered the aging process in the family environment and the factors that contribute to such an event. Articles published in the period from 2016 to 2020 were included, resulting in 11 (eleven) articles related to the objective of the study. Data analysis resulted in the following thematic categories: family, care and professional monitoring. It was observed through these studies that the aging process requires a special look, and the elderly should be offered a better quality of life, through the comfort of family members and professional monitoring, guaranteeing and promoting their physical, psychological and social well-being.